Optimization of thermal conditions in growing of GSO:Ce crystals by Czochralski technique - Krivoshein, V.I.; Martynov, V.P.; Nagornaya, L.L.; Ryzhikov, V.D.; Bondar`, V.G. (Functional Materials, 2005)
Crystallization conditions of gadolinium silicate Gd₂SiO₅:Ce have been studied depending on the crystallographic direction of the crystal growing in various thermal conditions. For the developed crystallization assembly, it is just the crucible position relative to the inductor upper turn has been shown to be the optimum one. Determined have been the growing parameters and regimes providing the obtained of high spectrometric quality of up to 50 mm in diameter and up to 150 mm length. The  40x40 mm² scintillators prepared from those crystals show the energy resolution 10.4 % under y irradiation with ¹³⁷Cs (662 keV). Исследованы условия кристаллизации силиката гадолиния Gd₂SiO₅:Ce в зависимости от кристаллографического направления их выращивания в различных тепловых условиях. Показано, что для разработанного кристаллизационного узла оптимальным является расположение тигля относительно индуктора на 5-7 мм выше верхнего витка индуктора. Определены параметры и режимы роста, позволяющие получать кристаллы диаметром до 50 мм и длинной до 150 мм высокого спектрометрического качества. Сцинтилляторы  40x40 mm² , изготовленные из этих кристаллов, показали энергетическое разрешение 10,4 % при облучении y-излучением ¹³⁷Cs энергией 662 кэВ.